HNF1A binds and regulates the expression of SLC51B to facilitate the uptake of estrone sulfate in human renal proximal tubule epithelial cells - Chan, Jun Wei (2023)
Renal defects in maturity onset diabetes of the young 3 (MODY3) patients and Hnf1a-/- mice suggest an involvement of HNF1A in kidney development and/or its function. Although numerous studies have leveraged on Hnf1α-/- mice to infer some transcriptional targets and function of HNF1A in mouse kidneys, species-specific differences obviate a straightforward extrapolation of findings to the human kidney. Additionally, genome-wide targets of HNF1A in human kidney cells have yet to be identified. Here, we leveraged on human in vitro kidney cell models to characterize the expression profile of HNF1A during renal differentiation and in adult kidney cells. We found HNF1A to be increasingly expressed during renal differentiation, with peak expression on day 28 in the proximal tubule cells. HNF1A ChIP-Sequencing (ChIP-Seq) performed on human pluripotent stem cell (hPSC)-derived kidney organoids identified its genome-wide putative targets. Together with a qPCR screen, we found HNF1A to activate the expression of SLC51B, CD24, and RNF186 genes. Importantly, HNF1A-depleted human renal proximal tubule epithelial cells (RPTECs) and MODY3 human induced pluripotent stem cell (hiPSC)-derived kidney organoids expressed lower levels of SLC51B. SLC51B-mediated estrone sulfate (E1S) uptake in proximal tubule cells was abrogated in these HNF1A-deficient cells. MODY3 patients also exhibit significantly higher excretion of urinary E1S. Overall, we report that SLC51B is a target of HNF1A responsible for E1S uptake in human proximal tubule cells. As E1S serves as the main storage form of nephroprotective estradiol in the human body, lowered E1S uptake and increased E1S excretion may reduce the availability of nephroprotective estradiol in the kidneys, contributing to the development of renal disease in MODY3 patients.